Transient near field of Hertzian dipole - Думин, А. Н.; Плахтий, В. А.; Вольвач, Я. С.; Думина, О. А. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
More accurate expressions for all components of near field of Herzian dipole are received by vector potential method in time domain. The comparison of the obtained expressions with classical ones is carried out. The time de- pendences of vector potential on observation point coordinates nearby the radiator are depicted for the classical, more accurate, and precise expressions calculated numerically for the case of stepwise exciting current.